Effects of a 2‐Year Application of Different Residual Biomasses on Soil Properties and Potato Yield. Issue 12 (17th October 2018) - Abdeldaym, Emad Abdelhameed; Traversa, Andreina; Cocozza, Claudio; Brunetti, Gennaro
Abstract : The increasing food demand encourages the overuse of agricultural lands and natural resources that often is not economic, social, and environmentally sustainable. This overuse can lead to the soil sickness, which causes the decline of the soil fertility through the development of soil‐borne diseases, the depletion of nutrients, and the loss of soil organic matter. Addition of residual biomasses is a good agricultural practice for improving soil properties and enhancing crop production, in the framework of a sustainable development. The study is performed in a 2 years field experiment using olive pomace residues (OPR), composts from municipal solid wastes (CMW), spent mushroom compost (SMC), and livestock manures based compost (BRX) for the fertilization of the potato crop. The aim of the study is to test the impact of different biomasses available in Apulia region, Italy, on soil fertility and potato growth. The application of BRX shows the highest potato yield in both seasons while OPR, CMW, and SMC significantly increases soil total nitrogen and organic carbon compared to BRX and un‐amended plots (CON). All treatments, except SMC, reduce the soil exchangeable K content, therefore, the application of BRX, OPR, and CMW should include the use of K based fertilizer to balance the high crop demand of K. Finally, SMC appears the best compromise for managing soil fertility and obtaining high potato yield. Abstract : Sustainable agriculture should be based on the use of residual biomasses for improving soil properties and enhancing crop production. The impact of different easily available biomasses on soil fertility and potato growth and yield is tested.